Softskill Development of Educational Staff in Providing Service for Student at UPN “Veteran” Jatim - S. Hardjati; A. Prathama; R. Febrianita (Nusantara Science and Technology Proceedings)
The development of human resources in an organization begins with the development of employee soft skill not to put aside the hard skills itself. Longsighted the growth of universities in Indonesia; it is necessary to strengthen the soft skill of human resources both in state and private universities. Universitas Pembangunan Nasional (UPN) "Veteran" Jawa Timur is a new state university. The status’s change of UPN "Veteran" Jatim from private to state continuing to enhance the term of human resource development, especially for the educational staff as more frontline that’s having direct contact with students toward providing service. This research focus is at UPN "Veteran" Jatim. The research method is descriptive qualitative with 12 informants of educational staffs from 7 faculties. The result shows that the educational staff at UPN Veteran Jatim have been supported by minimal training in soft skill and career development but optimally implementing the values of “Bela Negara”, Therefore it requires to develop a SMART model (Satisfaction, Measurement, Assurance, Responsibility, and Tangible). This model is found in research that has not been implemented by educational staff UPN Veteran Jatim.